Batteries: Highly Stretchable Separator Membrane for Deformable Energy‐Storage Devices (Adv. Energy Mater. 23/2018). Issue 23 (16th August 2018) - Shin, Myoungsoo; Song, Woo‐Jin; Son, Hye Bin; Yoo, Seungmin; Kim, Sungho; Song, Gyujin; Choi, Nam‐Soon; Park, Soojin
Abstract : In article number1801025, Nam‐Soon Choi, Soojin Park, and co‐workers fabricate a rubbery thermoplastic elastomer‐based stretchable separator membrane using non‐solvent induced phase separation. The membrane demonstrates a high stretchability of 270% strain, and a porous structure having a porosity of 61%. The as‐fabricated stretchable separator membrane is applied to both organic electrolyte‐based Li‐ion batteries and stretchable aqueous rechargeable Li‐ion batteries.